Preimplantation genetic testing for aneuploidy optimizes reproductive outcomes in recurrent reproductive failure: a systematic review - Mei, Youwen; Lin, Yonghong; Chen, Ying; Zheng, Jiafeng; Ke, Xue; Liang, Xuefei; Wang, Fang (Frontiers in Medicine, 2024)
Recurrent reproductive failure (RRF) is a common pregnancy complication, imposing great physical, emotional and financial burden for the suffered couples，which mainly included recurrent pregnancy loss (RPL) and recurrent implantation failure (RIF). The leading cause of RRF is believed to be aneuploid embryo, which could be solved by preimplantation genetic testing for aneuploidy (PGT-A) in theory. With molecular genetic development, PGT-A based on comprehensive chromosomal screening (CCS) procedures and blastocyst biopsy is widely applied in clinical practice. However, its effects in RRF were not defined yet. In the present review, we systematically analysed the effects of PGT-A based on CCS procedures and blastocyst biopsy in RRF, and tried to identify the suitable population of PGT-A by sub-analysis. We found that PGT-A could optimise the reproductive outcomes of RRF sufferers, especially in those with advanced age. However, in patients with multiple occurrences of pregnancy losses, the benefits of PGT-A were limited.